2012
DOI: 10.1016/j.ijom.2011.07.1071
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and dental stability of segmental distraction of the anterior mandibular alveolar process. A 2-year follow-up

Abstract: Clinical Paper Orthognathic SurgerySkeletal and dental stability of segmental distraction of the anterior mandibular alveolar process. A 2-year follow-up Abstract. 33 patients (27 females; 6 males) were retrospectively analysed for skeletal and dental relapse before distraction osteogenesis (DOG) of the mandibular anterior alveolar process at T1 (17.0 days), after DOG at T2 (mean 6.5 days), at T3 (mean 24.4 days), and at T4 (mean 2.0 years). Lateral cephalograms were traced by hand, digitized, superimposed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…13 In addition, the interface of the surgical section of the anterior aspect of the symphysis was more susceptible to resorption and bony remodelling. 2,14 In conclusion, this long-term follow-up of 5.5 years found that further change in soft tissues occurred between 2.0 and 5.5 years postoperatively regarding point B 0 and labrale inferior. The physiological process of ageing and loss of soft tissue elasticity should be considered as possible reasons.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…13 In addition, the interface of the surgical section of the anterior aspect of the symphysis was more susceptible to resorption and bony remodelling. 2,14 In conclusion, this long-term follow-up of 5.5 years found that further change in soft tissues occurred between 2.0 and 5.5 years postoperatively regarding point B 0 and labrale inferior. The physiological process of ageing and loss of soft tissue elasticity should be considered as possible reasons.…”
Section: Discussionmentioning
confidence: 56%
“…It is interesting to note that the amount and type (rotational vs. translational) of advancement in the same patient population examined earlier were not correlated with the amount of skeletal relapse measured at incision inferior or point B. 2,14 An important short-term effect of maxillofacial surgery and a confounding variable is postoperative swelling (oedema from retraction, irritations, and inflammation). For this reason, the immediate shortterm soft tissue profile changes measured on lateral cephalograms always include swelling and thickness of the orthodontic brackets.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…5,6 Recently, changes in skeletal stability, and soft tissue profile were analysed after DO of the anterior alveolar process. 7,8 Besides the clinical benefits of DO, complications such as neurosensory disturbances of the inferior alveolar nerve are possible. Neurosensory changes in the alveolar nerve were evaluated mainly in animal studies after DO of the whole mandible.…”
mentioning
confidence: 99%